Standardization strategy for quantitative PCR in human seminoma and normal testis - Neuvians, Tanja Pascale; Gashaw, Isabella; Sauer, Christian; Ostau, Christian Eike von; Kliesch, Sabine; Bergmann, Martin; Häcker, Axel; Grobholz, Rainer (Journal of biotechnology, 2005)
Housekeeping genes are commonly used as endogenous references in quantitative RT-PCR. Ideally these genes are constitutionally expressed by all cell types and do not vary under experimental conditions. Tissues of 9 normal testes and 22 classical pure seminoma were obtained for RNA-extraction. Real-time RT-PCR was used to examine the mRNA-expression of ubiquitin C, beta-actin, GAPDH, 18S ribosomal RNA (18S rRNA) and porphobilinogen-deaminase (PBGD). Additionally, 3 normal testicular tissues and 39 seminoma, including 1 normal testis and 17 seminoma of the RT-PCR group, were utilized for microarray analyses. Ubiquitin C (protein degradation) was down-regulated, GAPDH (carbohydrate metabolism), beta-actin (cytoskeleton), 18S rRNA (ribosome) and PBGD (porphyrin metabolism) were up-regulated in seminoma. A normalization of the target gene data with up-regulated housekeeping genes would equalize or underestimate up-regulated data and overestimate down-regulated data. We demonstrate that none of the investigated housekeeping genes is suitable for normalization of the target gene RT-PCR data, but may be essential for tumor metabolism in human seminoma. Further, we developed a standardization strategy, which is applicable to many experimental investigations.